A Recipe for Innovation - Zahari, Taha
Contrary to my initial belief, it is, however, not easy to prepare a dish which both looks and tastes good. In addition, I found out that many dishes are actually very complex to prepare, requiring a longer preparation time and a large amount of effort to manipulate a variety of ingredients to make them taste and look good.